The Use of SWOT Matrix in MSME Marketing Strategies: A Case Study of Lojjjik Experience Bar - Rahim, Muhammad; Mas Rasmini; Rani Sukmadewi (Universitas Indo Global Mandiri Palembang, 2024)
The aim of this research is to develop an advertising approach that can be applied to the Lojjjik Experience Bar. Through the use of the SWOT matrix, opportunities are obtained to maintain the sorganization's image, company facilities, maintain the quality of products and courier services to attract consumers, improve management capabilities and cooperation for agency needs, provide order delivery services for consumers, utilize technological advances. for advertising and marketing, serving the lower middle market by presenting unique programs or portions, and maintaining good relationships with suppliers or regions throughout the restaurant. The recommended priority advertising approach is to maintain company photos. Keywords: SWOT, Lojjjik Experience Bar, Marketing Strategy